Enhancing the Value Chain to Increase Customer Satisfaction and Build Successful Breast Imaging Practices. Issue 1 (25th February 2019) - Loving, Vilert A
Abstract: The US health care industry is increasingly shifting to a value seeking mindset. The breast imaging value chain elucidates how breast imaging radiologists generate and deliver value to their customers, who include both patients and referring health care providers. The breast imaging value chain can be used by radiologists to improve operational effectiveness and to plan new value creation strategically. The overarching goals are increased customer satisfaction and successful practices.